Bahasa Matematis Suku Makian Dalam dan Makian Luar: Suatu Studi Etnomatika - Nurul Fatih (Peneliti.net, 2023)
The Makian tribe is a tribe that inhabits Makian Island and part of the mainland of Kayoa Island, south of Halmahera, Indonesia. This area is in the district of North Maluku. The curse tribe is divided into two sub-tribes, namely the western curse and the eastern curse. Both have different languages, namely Jitine and Tabayana. There are a number of tribal cultures that are closely related to the context in learning mathematics, however, most of the educators have not explored the culture of swearing. Thus, this study aims to determine the cultural values contained in the regional language found in North Maluku, namely the island of curses regarding the mathematical language used in the tribes of internal swearing and external swearing. This study uses ethnographic studies by describing the study of mathematical objects in the elements of the Makian language, which are sourced from library research, field observations and interviews with several informants who understand the Makian language well to provide a deeper understanding of the results of the literature review collected. .